Green entrepreneurship through melon product diversification for economic independence of KWT Lestari, Gunung Kidul - Sulasmi; Andik Asmara; Titin Hera Widi Handayani; Ngadiyono (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2026)
This program is designed to improve the entrepreneurial capacity, technical skills, and environmental awareness of members of the Sustainable Women Farmers Community (KWT) in Semanu, Gunung Kidul. The program was implemented through a participatory approach that involved training in melon-based product processing, green entrepreneurship education, and intensive mentoring in business management and digital marketing strategies. Participants were trained to process melons into various value-added products such as drinks, jams, and healthy snacks, while considering environmentally friendly principles and raw material efficiency. The results of the program showed significant improvements in several aspects, namely technical product processing skills (88 percent), application of green entrepreneurship principles (83 percent), business management skills (75 percent), and digital marketing strategies (65 percent). The tangible impact of this activity is seen in the formation of three small business groups after the training, which achieved a sustainability level of 72 percent. This success demonstrates that training integrated with local potential and oriented towards environmental sustainability can be an effective strategy in strengthening the economic independence of village women. Thus, this program not only provides economic benefits but also encourages the creation of a sustainable empowerment model and contributes to inclusive and resilient rural economic development.